Impact of physical activity programs and services for older adults: a rapid review - Marina B. Pinheiro; Juliana S. Oliveira; Jennifer N. Baldwin; Leanne Hassett; Nathalia Costa; Heidi Gilchrist; Belinda Wang; Wing Kwok; Bruna S. Albuquerque; Luiza R. Pivotto; Ana Paula M. C. Carvalho-Silva; Sweekriti Sharma; et al. (BMC, 2022)
Abstract Background Knowledge of which physical activity programs are most effective for older adults in different sub-populations and contexts is limited. The objectives of this rapid review were to: 1) Overview evidence evaluating physical activity programs/services for older adults; and 2) Describe impact on physical activity, falls, intrinsic capacity (physical domain), functional ability (physical, social, and cognitive/emotional domains), and quality of life. Methods We conducted a rapid review of primary studies from 350 systematic reviews identified in a previous scoping review (March 2021: PEDro, MEDLINE, CINAHL, Cochrane Database). For Objective 1, we included intervention studies investigating physical activity programs/services in adults ≥ 60 years. Of these, we included good quality (≥ 6/10 PEDro scale) randomised controlled trials (RCTs) with ≥ 50 participants per group in Objective 2. Results Objective 1: Of the 1421 intervention studies identified from 8267 records, 79% were RCTs, 87% were in high income countries and 39% were good quality. Objective 2: We identified 87 large, good quality RCTs (26,861 participants). Overall activity promotion, structured exercise and recreation/sport had positive impacts (≥ 50% between-group comparisons positive) across all outcome domains. For overall activity promotion (21 intervention groups), greatest impacts were on physical activity (100% positive) and social outcomes (83% positive). Structured exercise (61 intervention groups) had particularly strong impacts on falls (91% positive), intrinsic capacity (67% positive) and physical functioning (77% positive). Recreation/sport (24 intervention groups) had particularly strong impacts on cognitive/emotional functioning (88% positive). Multicomponent exercise (39 intervention groups) had strong impacts across all outcomes, particularly physical activity (95% positive), falls (90% positive) and physical functioning (81% positive). Results for different populations and settings are presented. Conclusion Evidence supporting physical activity for older adults is positive. We outline which activity types are most effective in different populations and settings.